Burocracia e controle da escolas estaduais do Paraná: o registro de classes on-line - Baalbaki, Angela Aiche Kittlaus (2022)
The bureaucracy, present and rooted in the projects and systems implemented in school institutions created according to the interests of the ruling class and imposed by the State, is a reflection of educational public policies. In state public schools in Paraná, programs and systems, such as the Online Class Registration (RCORegistro de classe online), are tools for bureaucratization and control of school practices. This research focuses on the analysis of the bureaucratic processes materialized in the RCO and programs linked to it. The theoretical-methodological foundation is dialectical materialism, through bibliographical and documentary analysis, as well as a personal report of experience with the use of RCO in school. The general objective is to analyze the RCO as an instrument of control over education and the school. The specific objectives are: to know the main conceptions of the relationship between bureaucracy and the State; analyze and conceptualize RCO from a historical and dialectical perspective; describe how the union of workers in education of the State of Paraná (APP-Sindicato), has been advising on the RCO. The first chapter discusses concepts of State and bureaucracy under different conceptions. The second chapter analyzes the RCO and its bureaucratic role in the school, as well as the APP-Sindicato guidelines. Finally, considering the bibliographical research and school practice, the last part is dedicated to an analysis of the functioning of the RCO system and the programs linked to it, as well as the contradictions between the discourse of the proposals presented by the Secretary of Education of Paraná (Secretaria de Educação do Estado do Paraná - SEED-PR) and the system implemented in schools.